2008
DOI: 10.1002/hrm.20243
|View full text |Cite
|
Sign up to set email alerts
|

Employee reactions to gainsharing under seniority pay systems: The mediating effect of distributive, procedural, and interactional justice

Abstract: This study examines the effects of gainsharing under seniority‐based pay systems on employee attitudes in Korea. It is hypothesized that gainsharing, which emphasizes performance, employee participation, and cooperation enhances employee perceptions of distributive, procedural, and interactional justice, and that this, in turn, produces positive employee attitudes. The participants were a sample of individuals from five firms that combined seniority‐based pay and gainsharing incentives and five comparable firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 59 publications
0
21
0
2
Order By: Relevance
“…Taking into account the effects of organizational justice documented in previous research, since large pay dispersions in pay for performance programs lead to higher perceptions of justice we can expect that they would be also associated to lower turnover intentions (Lum et al, 2008), higher pay satisfaction (DeConick and Stilwell, 2004), stronger organizational identification (Kwon et al, 2008) and less counterproductive behaviors (Cohen-Charash and Spector, 2001). Although such effects need to be tested in future studies, our results suggest that higher financial investments in the pay for performance program that a company implements bring not only motivational and productivity gains, but also benefits on other organizational dimensions that are essential for its success.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Taking into account the effects of organizational justice documented in previous research, since large pay dispersions in pay for performance programs lead to higher perceptions of justice we can expect that they would be also associated to lower turnover intentions (Lum et al, 2008), higher pay satisfaction (DeConick and Stilwell, 2004), stronger organizational identification (Kwon et al, 2008) and less counterproductive behaviors (Cohen-Charash and Spector, 2001). Although such effects need to be tested in future studies, our results suggest that higher financial investments in the pay for performance program that a company implements bring not only motivational and productivity gains, but also benefits on other organizational dimensions that are essential for its success.…”
Section: Discussionmentioning
confidence: 94%
“…Besides the important role of organizational justice in determining employees job and especially pay -related satisfaction, other studies highlighted similar effects on other important dimensions, such as turnover intentions (Lum et al, 2008), organizational identification (Kwon et al, 2008) and work behaviors. Concerning the latter aspect, several studies and meta-analytic reviews showed that employees who perceive high levels of organizational justice in what concerns the ways they are treated by their company display less work withdrawal behaviors (Pinder, 2008), less counterproductive behaviors and engage in fewer conflicts (Cohen-Charash and Spector, 2001), are more motivated in their jobs (Cropanzano and Rupp, 2003) and consequently have higher work performances (Colquitt et al, 2001).…”
Section: Organizational Justicementioning
confidence: 84%
“…Distributive justice may be subject to associated part be an outcome of individual negotiating processes (Hornung, Glaser & Rouseau, 2010). individual and organizational outcomes (Kwon, Kim, Kang & Kim, 2008). Many previous studies on distributive justice have demonstrated its direct effects on employee attitudes, suggesting that distributive justice increases job satisfaction, organizational commitment and reduce intention to leave (Arnold, Landry, Scheer & Stan, 2009;Harvey & Haines III, 2005;Choil & Chen, 2007).…”
Section: Distributive Justicementioning
confidence: 99%
“…Interactional justice is important during the hiring decision, during the promotion processes and also while on the job. Kwon, Kim, Kang, and Kim (2008) focused on interactional justice to evaluate employee's reactions to different bonus systems and found that it mediated the relationship between pay satisfaction, organizational commitment, and turnover intentions. Interactional justice can be further broken down into two additional components: interpersonal, which is the fairness evaluation of the social exchanges during the process, and informational, which is the fairness evaluation of how knowledge is distributed.…”
Section: Nepotism and Organizational Justicementioning
confidence: 99%